Biochemical Profile of Macroalgae: Analysis of Primary Metabolites and Hydrocolloid Content in Oenaek Waters During the Dry Season - Demoor, Yustina Putri Tiara; Oedjoe, Marcelien Djublina Ratoe; Salosso, Yuliana (Aquaculture Department, University of Mataram, 2025)
Macroalgae are important components in coastal ecosystems, acting as primary producers, oxygen producers through photosynthesis, supporting biodiversity, and providing habitat for marine organisms. In addition to their ecological functions, macroalgae have great economic potential due to their bioactive compound content, including hydrocolloids and nutrient metabolites, which are utilized in the food, pharmaceutical, and cosmetic industries. Biochemical content such as protein, carbohydrates, and hydrocolloids in macroalgae varies greatly depending on species and environmental conditions, so site-specific research is needed. This study analyzed primary metabolites and hydrocolloid content of ten macroalgae species collected from the waters of Oenaek Village during the dry season. The parameters tested included water, ash, fat, protein, carbohydrate, and agar (in red algae) and alginate (in brown algae) content. The results showed that the water content ranged from 1.51% to 29.16%, ash ranged from 0.05%–0.58%, fat ranged from 5.4%–28%, protein ranged from 1.82%–8.54%, and carbohydrates ranged from 50.3%–87.92%. The highest agar content was found in Gracilaria gracilis (19.6%) and the highest alginate in Sargassum polycystum (33.96%). Green algae do not contain hydrocolloids but have the highest carbohydrate content. The biochemical profile indicates that macroalgae from Oenaek have great potential for industrial applications, especially as a source of hydrocolloids and nutritional compounds.